Effects of spiritual intelligence on employee performance, mediated by organizational citizenship behavior: a conceptual analysis - Osman-Gani, Aahad M.; Anwar, Md. Aftab (2014)
The pattern and scope of business are changing frequently these days. Smart managers play various creative roles to deal with this rapid change and development. Continuous innovation and generation of new ideas are now adding value to the strategic business management. Thus, it seems that fresh ideas and new intelligence are needed to help managers to manage better, and leaders to lead more effectively. Spiritual intelligence plays a significant role in helping the managers and employees to deal with this dynamic change in the business environment. Spiritual intelligence is defined as understanding the meaning and context of our behavior and action that makes mindful choices rather than enchaining us to respond reflexively to life’s demands. It has an influence over individual behavior that will have an effect on individual work performance. This conceptual paper analyzes the nature of relationship existing between spiritual intelligence and employee performance mediated by organizational citizenship behavior. No empirical study was found to have investigated the nature to relationships existing among various dimensions of spiritual intelligence and employee performance with mediating effects of organizational citizenship behavior. HRD and management scholars may take the initiatives to identify and evaluate the pertinent issues that can influence employee performance improvement through enhancing their dimensions of spiritual intelligence. Future research can also identify appropriate HRD interventions that can be used to improve employee performance through improving various dimensions of their spiritual intelligence and organization citizenship behavior.